Wacana Direktif dalam Video Iklan pada Channel Youtube Agung Hapsah - Darwisy, Dhiyo Ghani; Wuryaningrum, Rusdhianti; Syukron, Ahmad (Lingua Skolastika, 2023)
ABSTRACT This study describes directive discourse in advertising videos on the Agung Hapsah YouTube Channel. Agung Hapsah is a content creator who shows video tutorials, short films, daily videos, and advertising videos. Video advertisements that are displayed, there are advertising products such as electronic goods, applications, drinks. The video advertisement that is delivered contains directive discourse. Directive discourse is a series of utterances or sentences conveyed by speakers or writers to direct listeners or readers to do something. Directive discourse can be understood by knowing the context and function of directive discourse conveyed by Agung Hapsah to determine the authenticity of a discourse categorized as directive. In order to find the context, type, and function of directive discourse as a whole in this study, a descriptive qualitative research method was used. This study was analyzed using discourse analysis techniques with Tripp's theory. The results of this research relate to the description of the types of directive discourse, the context of directive discourse, and the function of directive discourse conveyed by Agung Hapsah in advertising products. The directive discourse is influenced by context to make it easier to convey advertisements that contain content.